Human rights from the perspective of the philosophy of historical reality - Rosillo Martínez , Alejandro (2025)
In this article, an understanding of human rights is developed from a complex paradigm, based on Ignacio Ellacuría’s Philosophy of Historical Reality. To this end, the scheme follows the text “Towards a conceptualization of human rights”, which consists of ten concepts. Each of these concepts is deepened, in connection with other texts by Ellacuría, to account for the way in which human rights are rethought from the Philosophy of historical reality.